Razumevanje koncepta "umiranja z dostojanstvom" pri medicinskih sestrah v paliativni oskrbi - Mimić, Alenka (Obzornik zdravstvene nege, 2013)
Introduction: During the last decades, the principle of respect for human dignity has played a crucial role in the emerging global norms relating to bioethics, and dying with dignity has became a goal which palliative care would like to achieve. However, the knowledge about nurses' understanding of the concept of human dignity has thus far not been fully explored into. Methods: The interpretative phenomenological analysis was used as a framework for analysing qualitative research data collected through semi-structured interviews from July to September 2011. The sample consisted of five palliative care nurses employed at the University Clinic of Respiratory and Allergic Diseases Golnik and Institute of Oncology Ljubljana. All the participants possessed either secondary, college or university education. Results: The results of the study identified the nurses' knowledge, attitude and management as the most significant factors in conserving human dignity. Contributing to the creation of the sense of dignity are patients themselves, nurses, physicians, family members and significant others whose paths intersect in specific circumstances. Discussion and conclusion: In order to ensure that all patients with life-limiting illness are treated with care and respect, receive quality palliative end-of-life care and die with dignity, a patient-friendly environment and adequate organization of healthcare provision is necessary. It is also essential to emphasize the importance of holistic care and to raise the awareness of palliative care among healthcare professionals and the general public.
Keywords: attitude; bioethics; bioetika; dostojanstvo; dying with dignity; human dignity; odnos; paliativna oskrba; palliative care; umiranje